Emotional Intelligence and Smoking Tendency in High School Adolescents in Sidoarjo - Lisa Sriwangi; Dwi Nastiti (Psikologia : Jurnal Psikologi, 2015)
The background of of this research was the tendency of smoking behavior that was not only dominated by adults, but also the youth (high school), both inside and outside of school. The purpose of this study was to investigate the relationship between emotional intelligence with a tendency to smoke at high school students. This study was a correlational study, the independent variable (X) was emotional intelligence, the ability to recognize our own feelings and the feelings of others, the ability to motivate oneself, as well as the ability to manage emotions well in ourselves and in relationships with others. The dependent variable (Y) was the tendency of smoking, which is the inclination to perform activities in accordance with the desire for an activity without any coercion from outside but from within the individual himself. The subjects of this study were students of class XII SMK 3 Buduran in Sidoarjo totaled 392 students, and the number of samples were 186 students (based on Table Krejcie with error level of 5%), which was taken by simple random sampling. Data collection instruments such as emotional intelligence scale and scale trends in smoking. Data were analyzed using statistical analysis Pearson Product Moment correlation. The analysis showed there was a significant negative relationship between emotional intelligence and trends in smoking (r = -0.711; ρ = 0.000; ρ <0.05). This result means, higher emotional intelligence, the lower the tendency of smoking in class XII SMK 3 Buduran in Sidoarjo, and vice versa.